Zdravila za zdravljenje bolezni prostate in mehurja - Obreza, Aleš (Farmacevtski vestnik, 2015)
The most important active ingredients for alleviating symptoms of overactive bladder and treating prostatic cancer are presented in the paper. The manuscript complements the articles on the treatment of benign prostatic hyperplasia, published in the December issue of the Slovenian professional journal Farmacevtski vestnik.
Keywords: prekomerna aktivnost sečnega mehurja; prostata; prostate; rak (medicina); antiholinergiki; mirabegron; taksani; gonadoliberinski receptorji; antiandogeni